Public Policies Of The Quality Management System And Its Influence On The Satisfaction Of The Plastic Surgery Service Of The Edgardo Rebagliati Martins Hospital 2021 – 2023 - Chau Ramos, Enrique Antonio (2025)
This research analyzes the influence of the Health Quality Management System Policies on people's satisfaction, in relation to the reconstructive plastic surgery service provided at the Edgardo Rebagliati Martins Hospital, in the period 2021 - 2023. For this, surveys are applied to a sample of 494 people who received said service and the relationship between said policies and the dimensions of user satisfaction such as professional treatment, information, management results, time, service accessibility, trust and tangible aspects involving service is examined. The results of this research show that the Health Quality Management System Policies significantly influence the satisfaction of people who access the service, mainly in the professional treatment and information provided in the care; however, in the tangible aspects involving the service, a low correlation is shown.